Farming and health management: prevention and policy measures - Le Breton A.D. (The use of veterinary drugs and vaccines in Mediterranean aquaculture, 2009)
In aquaculture, more than in other animal productions, prevention is a key issue in health management. The risk of diseases increases with the intensification of the production and can be controlled mainly through the implementation of sanitary or medical prophylactic programs. Sanitary prophylaxis relates to hygienic rules, cleaning and disinfection procedures, water treatment, but also good feeding and rearing practices. Medical prophylaxis is based on the use of immunomodulators and vaccines. Proper vaccination procedures and strategies today allow for the control of the main bacterial diseases and a reduction of the consumption of antibiotics. A recent and promising area of research concerns the use of probiotics in aquaculture, especially in larviculture when fish have not raised their ontogenic maturity and cannot be immunised.
The Use of Veterinary Drugs and Vaccines in Mediterranean Aquaculture, 2003/05/21-23, Izmir (Turkey)